Reading Tan Malaka's ideas in the context of Indonesian constitutional law - Yuwono, Ardi Tri; Bruijns, Peet (Privietlab, 2026)
The Indonesian Constitution faces various challenges, such as the potential for politicization, the court's dependence on state funding, and the public’s poor understanding of the constitutional judicial order. This study aims to provide a critical framework for studying Indonesian constitutionality from Tan Malaka's perspective. By using a philosophical-doctrinal approach combined with a critical textual analysis of Tan Malaka's key works, such as Madilog, Naar de Republiek Indonesia, and Gerpolek, as well as the Decision of the State Administrative Court Number 210/G/2021/PTUN.JKT, this study shows how its concepts of